Pupil's perspectives on female genital cutting abandonment in Harari and Somali regions of Ethiopia - Asresash D Abathun; Johanne Sundby; Abdi A Gele (BMC, 2018)
Abstract Background Female Genital Cutting (FGC) is a harmful traditional practice that affects the physical and mental health of girls and women in many ways. In Ethiopia, although both governmental institutions and None-Governmental- Institutions (NGOs) launched different campaigns against FGC, their effects on the peoples' attitudes towards the practice have not been deeply investigated yet. Hence, this study particularly aimed to investigate the pupils' perspectives on FGC abandonment in the Harari and the Somali Regional States of Ethiopia where the prevalence of the practice was thought to be high. Methods A school-based cross-sectional study was conducted in the Somali and the Harari Regional States of eastern Ethiopia from October to December 2015. While purposive sampling was implemented to select the study areas from the two Regional States, stratified random sampling method was used to select 480 study subjects from those areas. Results The findings showed that the participants who received information through multiple information channels were more likely to support the abandonment of FGC than those who received information from a single source (p < 0.05). Similarly, the findings indicated that school-based awareness campaigns and TV-based media communications were the main sources of information that influenced a high proportion of young people to support the abandonment of the practice. The findings revealed that the majority of the participants strongly supported the abandonment of FGC. Conclusions Multiple information channels that include school-based awareness campaigns were found to be the best way to support the abandonment of FGC. Although the study shows an impressive improvement among the school girls and boys in recognizing the harmful effects FGC, complete abandonment of the practice might not be easily achieved due to its deep-rooted nature. Thus, to quicken the perpetuation of FGC in the stated Regional States, awareness creating campaigns that change the attitudes of youths towards the practice should be delivered through various sources. In this regard, school-based education, school mini-media, social media, and using the co-curricular activities to uncover the danger of this harmful practice could play significant roles in changing the pupils' attitudes towards the practice.